Strength and durability of rapid set PVA fiber reinforced LMC for pavement repair. Issue 4 (May 2019) - Kim, Ki-Won; Yu, Chan; Han, Jae-Woong; Park, Chan-Gi
This study evaluated the strength properties, chloride ion permeability and abrasion resistance of styrene–butadiene latex-modified polyvinyl alcohol (PVA) fibre-reinforced rapid-set cement concrete (LMFRRSC) for application to emergency repair of concrete pavements. Experiments were conducted to measure the compressive strength, flexural strength, splitting tensile strength, bond strength, chloride ion penetration and abrasion resistance of LMFRRSC for variable PVA fibre content (0, 0.05 and 0.10%); test results showed that these test parameters increased with the volume fraction of PVA fibre, satisfying all traffic-opening criteria for emergency concrete pavement repair. The PVA fibre additive effectively minimized crack formation generated as a result of high hydration heat in the early material stages and inhibited fibre ball development. Thus, the addition of PVA fibre enhanced the performance of LMFRRSC for emergency repair of concrete pavements.